Markov chain application to the dynamics of the pelagic fishery along the Kerala coast, India - Srinath, M (Indian Journal of Fisheries, 2011)
The changing pattern of the composition of the pelagic fish assemblage in Kerala in the context of the introduction of the ring-seine gear has been modelled with the help of Markov chain model. The transition probabilities of the species dominance with respect to four dominant groups, namely, oilsardine, muckerel, whitebait and carangids before and after the introduction of the ring-seine have been estimated. The long term transition probabilities have also been computed with a view to predicting the status of the dominance of the major pelagic groups